Exploring the Split and Join Capabilities of a Robotic Collective Movement Framework. (2nd May 2013) - Navarro, Iñaki
Abstract The splitting and joining capabilities of a previously designed framework for the collective movement of mobile robots are studied. This framework is implemented in a distributed manner among the robots and allows scalability with increasing number of robots. It is expandable with new functionalities through the inclusion of new modules. Splitting functionality is created by including a new module, while joining does not need new structures. A total of 130 systematic experiments, grouped in six different sets, were undertaken to test the splitting and joining functions of the framework, yielding results in which robots behaved as expected. Four of the sets correspond to experiments in simulation using up to 40 robots. The remaining sets use eight real robots.